16Affect Theory. (5th November 2021) - Ahern, Stephen
Abstract: This chapter reviews important research in affect studies published in 2020, a year that saw the appearance of a rich selection of scholarly books that further develop the insights and methods of affect theory or that apply established approaches to investigations of affective phenomena in a variety of areas of study. The chapter is divided into the following sections: 1. Critique and Affect, which focuses on Critical Affect: The Politics of Method, by Ashley Barnwell; 2. Literary Affect, which focuses on Affect and Literature, edited by Alex Houen; 3. Cultural Histories of Affect, which focuses on Peculiar Attunements: How Affect Theory Turned Musical, by Roger Mathew Grant, and Unfelt: The Language of Affect in the British Enlightenment, by James Noggle; 4. Race and Political Affect, which focuses on Black Feelings: Race and Affect in the Long Sixties, by Lisa M. Corrigan, and Reading Affect in Post-Apartheid Literature: South Africa's Wounded Feelings, by Mark Libin; and 5. Reflections.